Anxiety, Enjoyment, and Adoption: Decoding Mobile Travel Shopping Intentions in Emerging Markets (International Journal of Food and Nutritional Sciences, 2022)
The rapid proliferation of smartphones and digital connectivity has transformed how consumers search, evaluate, and purchase travel and tourism products. Despite the exponential rise of mobile commerce in India, consumers continue to exhibit varying degrees of hesitation toward mobile shopping, particularly for high-involvement travel services. This study investigates the behavioral and technological determinants that shape consumers’ intention to engage in mobile shopping for travel and tourism products in India. Drawing on the Technology Acceptance Model (TAM) and affective dimensions of consumer behavior, the research integrates constructs such as mobile skillfulness, anxiety, enjoyment, usefulness, ease of access, and compatibility to explain mobile purchase intentions and patronage behavior. Using empirical data collected from 225 respondents across major tourist destinations, the findings reveal that mobile skillfulness significantly enhances enjoyment and perceived usefulness while reducing anxiety. In turn, enjoyment, usefulness, ease of access, and compatibility emerge as strong predictors of mobile shopping intention, which subsequently influences actual patronage. The study extends the classical TAM framework by embedding affective and skill-based variables, offering a holistic understanding of mobile shopping behavior in the travel domain. Managerially, the results highlight the need for intuitive mobile interfaces, enhanced user training, vernacular content, and trust-building mechanisms to mitigate anxiety and foster consumer engagement. The research contributes to the growing literature on mobile commerce adoption in emerging markets and provides actionable insights for marketers, tourism service providers, and policymakers promoting digital tourism ecosystems in India.